Importance of Magnetic Resonance Imaging With Diffusion-weighted Imaging in Guiding Biopsy of Nodular Ganglioneuroblastoma: A Case Report. Issue 1 (January 2021) - Jain, Neha; Halbert, Jay; Patel, Premal A.; Biassoni, Lorenzo; Anderson, John; Sebire, Neil; McHugh, Kieran; Barone, Giuseppe
Abstract : Background: Nodular ganglioneuroblastoma is a rare peripheral neuroblastic tumor of variable prognosis. Accurate diagnosis, staging, and risk categorization can be particularly challenging in patients with nodular ganglioneuroblastoma due to the inherent heterogeneity of these lesions. Case Presentation: We illustrate the use of diffusion-weighted magnetic resonance imaging to identify tumor nodules and guide tumor biopsy in an almost 5-year-old boy with a large abdominal tumor. Conclusions: Diffusion-weighted magnetic resonance imaging was successful in detecting and guiding biopsy of a poorly differentiated neuroblastoma nodule within the context of a well-differentiated ganglioneuroma, allowing the diagnosis and characterization of a ganglioneuroblastoma nodular, thus influencing the child's prognosis and treatment.